Knowledge, Attitudes and Practices of Health Workers and Caregivers Towards Retinopathy of Prematurity in Uganda: A Mixed‐Methods Study - Rebecca Claire Lusobya; Immaculate Atukunda; Andrew Weil Semulimi; Carol Nalukenge; Abubaker Kalinaki; Erima Denis; Mary Nyanzi; Charles Batte; David Mukunya; John Mukisa; Juliet Otiti‐Sengeri; Geoffrey Wabulembo (Wiley, 2024)
ABSTRACT Introduction Retinopathy of prematurity (ROP) is a significant global issue and a leading cause of preventable childhood blindness. Early screening and timely management of preterm babies at risk are crucial. To effectively implement this strategy, it is essential that caregivers and health workers are well‐informed about ROP. This study plays a vital role in assessing the knowledge, attitudes and practices of caregivers and healthcare workers towards ROP in Uganda, providing valuable insights into the current understanding and approach towards this condition. Method We conducted a sequential explanatory mixed‐methods study, involving 214 participants. This group included 12 paediatricians, 56 neonatal nurses and 146 caregivers, all of whom play crucial roles in the healthcare system. The study was conducted at two tertiary hospital neonatal clinics in Uganda. A researcher‐administered structured questionnaire was used to collect the data on the participants' knowledge, attitudes and practices. Descriptive statistics were used to describe variables, while qualitative data were analysed using thematic content analysis. Results We recruited 146 caregivers with a mean age of 29.4 (±standard deviation 6.5) years, 12 paediatricians with a median age of 37 years (IQR: 36-41) and 56 nurses with a median age of 35 years (30-42). The median working duration of health workers at the neonatal unit was 3 (IQR: 1.8-4.2) years. Thirty‐two (21.92%) caregivers and 28 (49.12%) health workers had good knowledge about ROP, whereas 9 nurses and 2 paediatricians did not know about ROP. Barriers to ROP screening included limited resources (equipment, time and skilled personnel) and limited parental involvement. Enhancing collaboration among medical care teams has the potential to improve ROP screening. Conclusion Insufficient knowledge about ROP among caregivers calls for increased efforts to educate and sensitise them about ROP and its risk factors.